2020
DOI: 10.3390/jcm9061631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronary Artery Calcification on Pre-Atrial Fibrillation Ablation CT Pulmonary Venograms and its Impact on Selection for Statin Therapy

Abstract: Atherosclerotic cardiovascular disease (ASCVD) shares many risk factors with atrial fibrillation (AF). Obtaining computed tomography images of the pulmonary veins (CTPV) before AF ablation procedures is common and can incidentally detect coronary artery calcification (CAC). The purpose of this study was to investigate the prevalence of CAC on pre-ablation CTPV, the frequency of CAC reporting on CTPV reports, and its impact on statin therapy among patients hospitalized for AF procedures. We retrospectively eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several studies have shown a high prevalence of coronary artery calcium (58-74%) in patients with AF who underwent CCT before pulmonary vein isolation for procedural planning [9,10,[14][15][16]. Chaikriangkrai et al [9] demonstrated that patients with AF had a higher prevalence of coronary artery calcium when compared to controls with normal sinus rhythm presenting with chest pain (74% vs. 63%, p < 0.001), despite similar CV risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a high prevalence of coronary artery calcium (58-74%) in patients with AF who underwent CCT before pulmonary vein isolation for procedural planning [9,10,[14][15][16]. Chaikriangkrai et al [9] demonstrated that patients with AF had a higher prevalence of coronary artery calcium when compared to controls with normal sinus rhythm presenting with chest pain (74% vs. 63%, p < 0.001), despite similar CV risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Additional coronary evaluation is not a required protocol during pre-ablation cardiac CTA but CACS is an often available parameter on pre-ablation scans focusing on pulmonary vein morphology. CAC was visually detected at a very high, 70.1% among the 638 patients with atrial fibrillation in Dunleavy et al .’s publication [ 12 ]. Visual CACS estimation was also used in the study of Hillerson et al ., where 59.6–63.5% CAC was found on 278 non-gated CT scans retrospectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that at least 10%, or in some publications even 70% of patients with atrial fibrillation have CAD [11][12][13][14]. Most of these referred publications used different definitions to determine the presence of CAD with lower spatial resolution CT scans assessing only a few hundred patients [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%